Pioneros de la responsabilidad social empresarial en Colombia (2011)
Although it can be argued that the term Corporate Social Responsibility (CSR) is new, in Colombia this concept has more than one hundred years of development. It was spontaneously arise as a projection of the sensitivity of some entrepreneurs who felt that, transcending the activities normally carried out, some of them also pioneers in the field of industrialization could bring something more to society. From these concerns came important developments in the field of education, medicine, general health and social housing. This article seeks to outline the contribution made by five industries visionary and committed to the community, in a period from the last years of the nineteenth and early twentieth centuries, a series of initiatives planned even to this day.